Laparoscopic Surgical Techniques for Endometriosis and Adenomyosis. Issue 4 (2000) - Wood, C.; Maher, P.; Woods, R.
Abstract : The details of surgical techniques for laparoscopic removal of endometriosis and adenomyosis are described briefly in textbooks and gynaecological journal articles. We have described a wide variety of techniques for the various procedures required in the treatment of endometriosis and adenomyosis, excluding hysterectomy. The principles are based upon those used in removal of primary cancer lesions. The limitations of thermal ablation are discussed, and evidence of improved results after excision of lesions have been submitted for publication.